Relationship between low response to clopidogrel and periprocedural ischemic events with coil embolization for intracranial aneurysms. (24th June 2015) - Asai, Takumi; Miyachi, Shigeru; Izumi, Takashi; Matsubara, Noriaki; Haraguchi, Kenichi; Yamanouchi, Takashi; Ota, Keisuke; Shintai, Kazunori; Tajima, Hayato; Wakabayashi, Toshihiko
Abstract : Objectives: Low response to antiplatelet drugs is one of the risk factors for ischemic events. We examined the influence of low response to clopidogrel on symptomatic ischemic events and new ischemic MRI lesions with endovascular intracranial aneurysmal coil embolization. Materials and methods: Between August 2010 and July 2013, 189 procedures in 181 consecutive patients who underwent endovascular coiling and received clopidogrel before treatment were investigated retrospectively. Platelet aggregation activity was examined by VerifyNow analysis. Low response to clopidogrel was defined as P2Y12 reaction units ≥230 in this study. Symptomatic ischemic complications within 30 days and postoperative new ischemic lesions on MRI–diffusion weighted imaging were evaluated. Results: 66 of 189 (34.9%) cases were low responders to clopidogrel. Ischemic complications occurred in 2 of 66 (3.0%) low responders compared with 6 of 123 (4.9%) responders (p=0.72). A new high intensity spot larger than 5 mm was significantly more frequent in low responders (26 of 66; 39.4%) than in responders (26 of 121; 21.2%; p=0.01). On multivariate analysis, independent risk factors for larger new ischemic lesions were low response to clopidogrel, smokers, posterior location, and aneurysms with a larger neck. Conclusions: Low response to clopidogrel had little effect on clinical outcome although it increased asymptomatic large ischemic lesions in this cohort.